Psycho-behavioral manifestations of Burnout in workers of an average complexity hospital - Gabriela Machado Ezaias; Maria do Carmo Lourenço Haddad; Marli Terezinha Oliveira Vannuchi (Universidade Federal do Ceará, 2012)
Burnout is a psychological syndrome that occurs due to chronic emotional stress in the work process, and can be expressed by several types of signs and symptoms. This is a quantitative descriptive study that aimed to identify and relate behavioral and psychological symptoms with the positive dimensions of professional burnout syndrome in a public hospital of medium complexity. To collect data we used a self-administered instrument, constituted of the main dependent variables of burnout syndrome, created by Christine Maslach and validated in Brazil by Benevides-Pereira in 1986, and to identify the signs and symptoms of burnout syndrome we used the questionnaire developed by Menegaz. The data analysis to find relationships between the dimensions of the syndrome and symptoms researched with significant values by applying the chi-square test, showing the effect of psychological distress in productivity and quality work.